Plover parents care more for young of the opposite sex. (5th April 2018) - Lees, Daniel; Sherman, Craig D H; Kostoglou, Kristal; Tan, Laura X L; Maguire, Grainne S; Dann, Peter; Weston, Michael A
Abstract : We examine the effect of brood sex-ratio on parental care of a ground-nesting shorebird. Females care most for the young during the first half of brood-rearing, steadily reducing care. Males contributed little care early during brood-rearing, increasing care as young approach fledging. Brood sex-ratio influenced the division of care; males care more for their daughters, females care more for their sons. Abstract: Within some socially monogamous species, the relative contribution of care provided by each parent varies substantially, from uniparental to equitable biparental care. The provision of care is influenced by its costs and benefits, which may differ between parents (leading to inter-parental "conflict") and are expected to change in relation to the needs of young (which vary with age) and potentially to traits such as their sex. If the fitness benefits to parents differ with the sex of offspring, parents may adjust their investment in young of different sexes to optimize their own fitness. We radio-tracked 42 Red-capped Plover Charadrius ruficapillus broods and found that, at least diurnally, females cared for the brood for the first half of brood-rearing, while gradually reducing care. Males contributed little diurnal care early in brood-rearing, then increased care, taking over from females as young approached independence. The sex-ratio of the brood influenced the division of care between parents; male parents attended the brood more when there were greater proportions of female chicks, whereas female parents attended the brood more when there were a greater proportion of male chicks. This is apparently the first recorded case in a precocial bird where each parents' investment in brood care is influenced by the brood sex-ratio. Our results defy unambiguous explanation.